2004
DOI: 10.1073/pnas.0404100101
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of matrix metalloproteinase-9 for the transformation of human mammary epithelial cells by Stat3-C

Abstract: Persistently activated Stat3 is found in many different cancers, including Ϸ60% of breast tumors. Here, we demonstrate that a constitutively activated Stat3 transforms immortalized human mammary epithelial cells and that this oncogenic event requires the activity of matrix metalloproteinase-9 (MMP-9). By immunohistochemical analysis, we observe a positive correlation between strong MMP-9 expression and tyrosine phosphorylated Stat3 in primary breast cancer specimens. These results demonstrate a relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
200
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(211 citation statements)
references
References 39 publications
10
200
0
1
Order By: Relevance
“…In agreement with our study, S100A8 and S100A9 were shown to induce myeloid cell recruitment and tumor cell invasion in premetastatic lung (19). Interestingly, expression profiling of signal transducers and activators of transcription 3 -transformed MCF10A and HME breast epithelial cells identified 23 overexpressed genes including MMP-9, S100A8, and S100A9 (32). Taken together, S100A8 and S100A9 may serve as potential markers associated with tumor cell invasion and migration.…”
Section: Discussionsupporting
confidence: 74%
“…In agreement with our study, S100A8 and S100A9 were shown to induce myeloid cell recruitment and tumor cell invasion in premetastatic lung (19). Interestingly, expression profiling of signal transducers and activators of transcription 3 -transformed MCF10A and HME breast epithelial cells identified 23 overexpressed genes including MMP-9, S100A8, and S100A9 (32). Taken together, S100A8 and S100A9 may serve as potential markers associated with tumor cell invasion and migration.…”
Section: Discussionsupporting
confidence: 74%
“…40 BcL-xL is one of the important regulators of apoptosis and is involved in the regulation of the cell cycle, prolongs cell survival and inhibits apoptosis. Stat3 normally resides in the cytoplasm and can be activated through phosphorylation by cytokines, growth factors and oncogenic proteins.…”
Section: Discussionmentioning
confidence: 99%
“…RNAi caused by synthetic siRNAs is transient due to lack of tumor-targeting and degradation of siRNA. 40 However, this problem has been solved here by using plasmid expression vectors in Salmonella as a delivery tool. These plasmid vectors produce sufficient amounts of shRNA using normal cellular machinery, 41 and are able to knockdown expression of target genes for extended periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 STAT3 regulation of matrix metalloproteinase-2 (mmp-2) correlates with invasiveness of melanoma cells, 38 and activation of mmp-9 is required for STAT3-induced transformation of mammary epithelial cells. 50 Thus STAT3 and STAT5 contribute to cancer by activating genes that promote cell cycle entry and cell survival, among other cellular processes (Fig. 1).…”
Section: Stat Signaling and Cancermentioning
confidence: 99%
“…To directly evaluate the contribution of STAT3 to transformation of mammary epithelial cells, STAT3-C was expressed in these cells. 50 In two independent immortalized mammary epithelial cell lines, MCF10A and HMECs, STAT3-C expression led to transformation. To identify the changes in gene expression associated with this transformation, the expression profile of cells expressing STAT3-C was compared to cells expressing empty vector using Affymetrix oligonucleotide microarrays.…”
Section: Genome-wide Analysis Of Stat Targetsmentioning
confidence: 99%